PENERAPAN KNOWLEDGE MANAGEMENT PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) KOTA PEKANBARU - Yeni Anrina Harahap; Tuti Harahap Khairani Harahap (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Regional Development Planning Agency (Bappeda) of Pekanbaru city is one of the local government institutions accordance with their tasks to help heads of regions in organizing of government in development planning. Regional development planning must reflect the reality of the needs of an area, which be functioning as a plan to improve the use of available public resources in the region. One of the problems that occur is Bappeda can not be separated from the various constraints such as the lack of documents availability of study results or study to formulate the development planning program. There are still a lack of quantity and quality of human resources in the Bappeda environment, so it is difficult to make a quality and on time planing. Meanwhile, high and rapid of development and growth of the Pekanbaru city which must be balanced by Bappeda to produce planning products that can answer development and changes of region in the future. By applying the knowledge management is believed to have an important role in helping to improve the effectiveness of Bappeda because it can encourage the use of prior knowledge to improve the quality of decision making process. In addition, knowledge management can also serve as a tool in the process of organizational change, because the knowledge management can help to build a culture of learning within an organization. Learn to perform activities which they are responsible should be getting better over time. Based on this, researchers interested in conducting a qualitative research on the application of knowledge management in Bappeda Pekanbaru City.Theoretical concept used by the author is the theory of knowledge management Ismail Nawawi are: human, process, technology, content and the factors that affect the implementation of knowledge management in the organization. This study used a qualitative research with descriptive study. In collecting the data, the researcher used interview, observation and documentation.The results of this study indicate that Bappeda has implemented knowledge management, although there are still deficiencies in the implementation process, for example such as lack of awareness to share information among employees outside the meeting activities. But the advantages are Bappeda continue to make changes for the better as the enactment of theimplementation of an online system to provide information of evelopment activities to the society which is currently only up to the district level.Key words: Application, Knowledge Management, Development Planning